2022
DOI: 10.3390/toxins14080571
|View full text |Cite
|
Sign up to set email alerts
|

A Long-Read Genome Assembly of a Native Mite in China Pyemotes zhonghuajia Yu, Zhang & He (Prostigmata: Pyemotidae) Reveals Gene Expansion in Toxin-Related Gene Families

Abstract: Pyemotes zhonghuajia Yu, Zhang & He (Prostigmata: Pyemotidae), discovered in China, has been demonstrated as a high-efficient natural enemy in controlling many agricultural and forestry pests. This mite injects toxins into the host (eggs, larvae, pupae, and adults), resulting in its paralyzation and then gets nourishment for reproductive development. These toxins have been approved to be mammal-safe, which have the potential to be used as biocontrol pesticides. Toxin proteins have been identified from many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 70 publications
1
8
0
Order By: Relevance
“…In ectophagous idiobiont parasitoids, reproductive females inject venom that permanently paralyzes the hosts and rapidly suppresses their immune responses 29,31,47–54 . Suppression of host immune responses by parasitoids may impose host physiology changes which alter host immature development and affect adult longevity and fecundity 47,52,55–59 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In ectophagous idiobiont parasitoids, reproductive females inject venom that permanently paralyzes the hosts and rapidly suppresses their immune responses 29,31,47–54 . Suppression of host immune responses by parasitoids may impose host physiology changes which alter host immature development and affect adult longevity and fecundity 47,52,55–59 .…”
Section: Discussionmentioning
confidence: 99%
“…In ectophagous idiobiont parasitoids, reproductive females inject venom that permanently paralyzes the hosts and rapidly suppresses their immune responses. 29,31,[47][48][49][50][51][52][53][54] Suppression of host immune responses by parasitoids may impose host physiology changes which alter host immature development and affect adult longevity and fecundity. 47,52,[55][56][57][58][59] In this study, we demonstrated that P. zhonghuajia parasitism has lethal, sublethal and transgenerational effects on the PTM.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations